Perancangan dan Analisa Kinerja Fiber to the Building (FTTB) untuk Mendukung Smart Building di Daerah Urban - anggita, trivia; Rahman, Liani Budi; Akbar, Anshari; Laagu, Muh Asnoer; Apriono, Catur (Faculty of Engineering, Universitas Tanjungpura, 2020)
The development of digital technology makes it easy for humans to do activities, including compliance with the requirement of voice, data, and video communication in office buildings. Infrastructures are a primary consideration for a reliable connection, large-capacity, and stable communication lines. Recently, Fiber-optic communication systems are now the backbone of information signal delivery technology. This paper proposes a design of optical fiber transmission media for deployment in urban office buildings. It has been called fiber to the building (FTTB), which uses a fiber optic communication system to support the availability of multimedia network in an office area. A typical office building in an urban area has a multilevel structure that is used by various companies with multimedia network access services to support business activities. This study considers XGPON technology as a fiber optic-based broadband access technology that is deemed appropriate to the needs of the use of a multimedia network. The design begins with conducting a data collection survey. The next is the chosen device components based on the estimated distribution of the number of users. There are three parameters will be calculated include Power Link Budget (PLB), Rise Time Budget (RTB), and Bit Error Rate (BER), to determine the design feasibility. Based on PLB, RTB, and BER data, the proposed fiber to the building (FTTB) can meet the parameters to be achieved in the design, namely PLB of -27,24 dBm for downstream and -11,68 dBm for upstream, the value of is 0,049 ns, and value of BER is 0,186 x 10-1085. The design of FTTB can meet the requirement of users with a bandwidth of 9014,4 Mbps for 1200 users.